Balancing welfare and habitat damage in pigs (Sus scrofa) under extensive farming: an ethological approach for determining the effects of group composition and environmental enrichment - Collarini, Edoardo; Capponcelli, Luca; Pierdomenico, Andrea; Cordoni, Giada; Norscia, Ivan (Frontiers in Ethology, 2024)
According to the modern perspective on evaluating animal welfare, it is important to consider both negative and positive experiences. This study investigated the impact of group composition and environmental enrichments on the behaviours of free-ranging pigs, focusing on anxiety-related behaviours, aggression, affiliation, post-conflict affiliation, excavation, and non-invasive exploration activities. Data were collected on three different groups (all-female: N=10; all-male: N=13; mixedsex: N=12) of free-ranging pigs raised in a natural woodland habitat at the ethical farm "Parva Domus" (Turin, Italy). To evaluate the impact of environmental enrichment, further data collection was carried out on the mixed-sex group under three different enrichment conditions (absence; dry leaves; straw) provided in a rotational scheme. Group composition did not affect levels of anxietyrelated behaviours, aggression and non-invasive exploration. However, it did impact other social aspects (affiliation: One-way ANOVA: p=0.003; post-conflict affiliation: Kruskal-Wallis: p=0.005).In particular, the mixed-sex and the all-male groups showed higher levels of affiliation than the allfemale group and the mixed-sex group showed higher levels of post-conflict affiliation than the allmale group. Moreover, we found differences in excavation behaviour levels (Kruskal-Wallis: p=0.001), with higher levels of excavation behaviour in the mixed-sex group compared to the allfemale group. Regarding the impact of enrichments, we found differences in levels of anxiety-related behaviours (One-way ANOVA: p = 0.046), affiliation (One-way ANOVA: p = 0.006), excavation (One-way ANOVA: p<0.001) and non-invasive exploration activities (One-way ANOVA: p<0.001).In enrichment conditions with straw, we found a significant decrease in anxiety-related, affilliation and excavation behaviours levels, and a significant increase in non-invasive exploration behaviours.A trend with lower levels of aggression was observed in straw enrichment condition compared to the absence of enrichment, although the difference was not significant. Moreover, there were no differences in post-conflict affiliation frequencies. Our findings suggest that forming mixed-sex groups and providing environmental enrichments such as the straw could be suitable solutions to effectively reduce invasive excavation behaviours without preventing pigs from expressing their natural behavioural repertoire, thus maintaining high standards of animal welfare. This study highlights behavioural aspects to be considered in the extensive farming, confirming the importance of ethology as a tool for assessing pig welfare.